1996
DOI: 10.1093/molehr/2.10.733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of γ-aminobutyric acid on human sperm motility and hyperactivation

Abstract: This study was undertaken to evaluate the effects of gamma-aminobutyric acid (GABA) and GABAergic agonists and antagonists on sperm kinematic parameters and hyperactivation, evaluated by a computer-assisted semen analysis (CASA) system, and intracellular cAMP content in 22 normozoospermic semen samples. Because of the possible interaction of progesterone with the GABAA receptor, we also evaluated the effects of progesterone on these parameters. GABA increased beat cross frequency, curvilinear velocity (VCL), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 30 publications
2
76
0
Order By: Relevance
“…S3, Bottom panels and Table S6). In capacitated spermatozoa, P4 stimulation increased VCL by 12%, comparable to numbers reported earlier (7,21), but VCL values remained unchanged in the presence of PregS, pristimerin, or lupeol alone (Fig. S3A, Top and Inset and Table S6).…”
Section: Pristimerin and Lupeol Decrease Sperm Hyperactivation In Thesupporting
confidence: 87%
“…S3, Bottom panels and Table S6). In capacitated spermatozoa, P4 stimulation increased VCL by 12%, comparable to numbers reported earlier (7,21), but VCL values remained unchanged in the presence of PregS, pristimerin, or lupeol alone (Fig. S3A, Top and Inset and Table S6).…”
Section: Pristimerin and Lupeol Decrease Sperm Hyperactivation In Thesupporting
confidence: 87%
“…It has been shown that GABA increases capacitation in guinea pig and ejaculated human sperm and ram sperm [De las Heras et al 1997;Zhang et al 2000]. Moreover, GABA also increases hyperactivated motility in ejaculated human spermatozoa [Calogero et al 1996;Ritta et al 1998;Zhang et al 2000]. Importantly, in some cases stimulation by a GABA A receptor agonist or inhibition by a GABA A receptor antagonist was also observed [Calogero et al 1996;Ritta et al 1998;Zhang et al 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GABA also increases hyperactivated motility in ejaculated human spermatozoa [Calogero et al 1996;Ritta et al 1998;Zhang et al 2000]. Importantly, in some cases stimulation by a GABA A receptor agonist or inhibition by a GABA A receptor antagonist was also observed [Calogero et al 1996;Ritta et al 1998;Zhang et al 2000]. As discussed above, progesterone also increase capacitation and hyperactivated motility of ejaculated human and porcine sperm, but data linking the effect to the GBRCs have not been reported [Meizel 2004].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations